THE ADOPTION OF BUSINESS DIGITALIZATION BY SMEs: A CASE STUDY IN BANDUNG - Ferdi Z Azan; Hantoro Ksaid Notolegowo; Nurfahmiyati; Nunung Nurhayati (UPT Publikasi Ilmiah UNISBA, 2024)
The objective of this study is to investigate the the existing practice of business digitalization by SMEs in Bandung. There were qualitative techniques employed in conducting the research, which mainly consisted of several interviews with small scale enterprise owners cutting across different sectors. The findings show that digital enterprises are responsible for significant improvements in business operations and financial results. However, there are still some challenges including high costs at initiation stage and inadequate employee skills required. According to research affordable technology solutions and training employees can be effective approaches to mitigate these obstacles thereby improving Small Medium Enterprises benefits from going digital.